Rural palliative care transitions from home to hospital: Carers' experiences. (August 2014) - Hatcher, Isabelle; Harms, Louise; Walker, Brigid; Stokes, Suzanne; Lowe, Alison; Foran, Kellie; Tarrant, Jacqui
Abstract Objective To document carer perceptions of patients' transitions from community to hospital‐based palliative care in a rural setting. Design A qualitative study using an interview method at two time points. Setting Rural palliative care providers: Kyneton District Health Service and the Macedon Ranges Palliative Care Service, Victoria Participants Six adult caregivers of six palliative care patients who had cancer were interviewed, three of whom were male and three female. Main outcome measures Semistructured interviews were conducted exploring the caregivers' decisions to transition to hospital‐based care and their perceptions of the transition to hospital and the hospital‐based care these patients received. Results Thematic analysis revealed that carers made the decision for the patient in their care to transfer from home to hospital care. Carers experienced the transition to hospital care positively, particularly in relation to the communication of the patient's care needs. While communication issues arose while in hospital, they were not related to the transitional aspects of the palliative care service. Conclusions The findings from this small, exploratory study suggest that these carers benefited from the new model of rural palliative care service provision. A large‐scale, mixed‐method study would enable more generalisable findings to be established.